2022
DOI: 10.1002/pra2.644
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Personality Traits in Human‐Humanoid Robot Interaction

Abstract: With the advancement of science and technology, humanoid robots have been gradually adopted in human society. Given the human‐like appearance, the perceived personality of a humanoid robot can affect humans' general perceptions of the robotic agent, and even task performance. However, limited research pays attention to examining how a humanoid robot's non‐verbal cues characterize its personality traits. To solve this gap, this research aims to investigate how to use humanoid robots’ non‐verbal features (textua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Robot personality is also a potential research direction for HRE studies. Research on robot personality has shown that humans tend to project personality onto robots (Fussell et al, 2008) as well as recognize a robot's personality through its designs (Chien et al, 2022). Our interview data also demonstrated that some participants projected a robot personality onto the robot, such as the “friendly” mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Robot personality is also a potential research direction for HRE studies. Research on robot personality has shown that humans tend to project personality onto robots (Fussell et al, 2008) as well as recognize a robot's personality through its designs (Chien et al, 2022). Our interview data also demonstrated that some participants projected a robot personality onto the robot, such as the “friendly” mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Personality detection aims to identify the personality traits implied in social media posts that offering a deeper insight into human behavior (Nutescu and Mocanu 2023), emotional processes (Lian, Liu, and Tao 2022), and mental health (Zanwar et al 2023). Besides, it can provide timely and objective support for downstream applications, such as human-computer interaction systems (Chien, Chen, and Chan 2022), virtual dialogue systems (Yang, Chen, and Narasimhan 2021), and recommendation systems (Yang et al 2022;Shen et al 2020).…”
Section: Introductionmentioning
confidence: 99%